Nucleotide sequence of Escherichia coli K-12 replication origin. - Sugimoto, K (1979)
From subfragments of an EcoRI fragment (9 kilobase pairs) that contained the replication origin of the Escherichia coli chromosome and had been cloned as a recombinant with a nonreplicating DNA fragment coding for ampicillin resistance, small derivative plasmids were constructed. The smallest of these, pTSO151, contained a segment of 463 base pairs as the chromosomal component. Another plasmid, pSY134, constructed from BamHI digests of the EcoRI fragment and mini-F(pMF21), contained a region of 422 base pairs identical with a corresponding region in pTSO151. We conclude that the replication origin of E. coli chromosome is located within this 422-base-pair segment. The nucleotide sequence of this segment is presented.